Incidência de mosca-minadora e insetos vetores em sistemas de manejo de pragas em tomateiro - Pratissoli, Dirceu; Carvalho, Jose Romario de; Pastori, Patrik Luiz; Oliveira de Freitas Bueno, Regiane Cristina [UNESP]; Zago, Hugo Bolsoni (Univ Federal Ceara, Dept Geol, 2015)
Arthropods considered viral vectors are early pests in the tomato crop and have the ability to cause direct or indirect damage, especially when there are failures in their management. The aim of this work was to study the incidence and infestation of viral vectors in two systems of pest management for crops of staked tomato. The experiment was carried out on plants of the 'Deborah Mix'of tomato from the 'Santa Clara'group, at a spacing of 1.0 x 0.5 m (rows x plants) under twin- stake, vertical training. The systems evaluated were: Ecological Pest Management (EPM) - with pests being monitored and the decision to apply insecticides made based on the level of infestation; and Conventional - programmed applications, started seven days after transplanting and then carried out twice a week. The highest incidence of B. tabaci occurred under EPM, whereas the greatest incidence of Liriomyza sp. and other species of aphids was seen under the conventional system; for F. schultzei however, no difference was seen for the two systems. Viral vector infestation was seen throughout the crop-training period, but overall, considering all insect pests, there was an 88.14% reduction in the number of applications under MEP. The adopted management system does not affect the incidence or infestation of viral vectors in the crop, but implementation of the MEP system enables a judicious use of pesticides, allowing a reduction in the number of applications, with a consequent reduction in production costs.

Os artrópodes considerados vetores de viroses são pragas iniciais na cultura do tomateiro e possuem capacidade de causar danos diretos e indiretos, principalmente quando ocorrem falhas no manejo. O objetivo deste estudo foi estudar a incidência e infestação de vetores de viroses em dois sistemas de manejo de pragas em plantios de tomateiro estaqueado. O experimento foi conduzido em plantio de tomateiro da variedade 'Débora Mix', grupo Santa Clara, com espaçamento de 1,0 x 0,5 m (linhas x plantas), em condução com duas hastes (Tutoramento vertical). Os sistemas avaliados foram: Manejo Ecológico de Pragas (MEP) - monitoramento das pragas e tomada de decisão para a aplicação de inseticidas com base no nível de infestação e Convencionalcalendário de aplicações que iniciaram sete dias após o transplantio e seguiram sendo realizadas duas vezes por semana. A maior incidência de B. tabaci ocorreu no sistema MEP, enquanto que a maior incidência de Liriomyza sp. e diferentes espécies de pulgões ocorreu no sistema convencional, mas para F. schultzei não houve diferença na incidência entre os manejos. Houve infestação dos vetores de viroses durante todo o período de condução da cultura e, no geral, considerando todos os insetospraga, a redução no número de aplicações foi de 88,14% no MEP. O sistema de manejo adotado não interfere na incidência e infestação de vetores de viroses na cultura, mas a implantação do sistema MEP viabiliza a utilização criteriosa dos defensivos agrícolas, permitindo redução do número de pulverizações com consequente redução dos custos de produção.
Incidence of leaf miner and insect vectors for pest management systems in the tomato
Keywords: Pest management; Bemisia sp.; Liriomiza sp.; Frankliniella sp.; Aphids; Pragas-manejo; Bemisia sp.; Liriomiza sp.; Frankliniella sp.; Afídeos